PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEBSITE GOOGLE SITES DALAM MENINGKATKAN HASIL BELAJAR - Stevi Wulandari; Ni'matuz Zuhroh (Dinamika Sosial: Jurnal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The development of technology certainly has a major impact on the world of education, one of which is the innovation of learning media. The existence of this learning media innovation, the teacher can increase student learning motivation which will also have an impact on student learning outcomes. This study to develop interactive learning media based on the google sites website in improving learning outcomes in social studies subjects at Ngebruk Islamic Junior High School. The method used is the R&D method. This study used 3 classes, namely the experimental class, the experimental class and the control class with 20 students. The results obtained in the experimental class through the pre test post test, namely the pre test value of 77.8 post test of 82.7. The control class had a pre-test score of 73.2, post-test 80.6. For the validation assessment, media experts get a score of 94%, material experts, 78%, social studies teachers 78%, student responses 80%-100%. It can be concluded that the implementation of the learning media on the google sites website can improve learning outcomes in social studies subjects at the Ngebruk Islamic Middle School. Then it can be said that this development media is feasible and does not need revision and the responses of students who feel happy. Abstrak Perkembangan teknologi tentunya memiliki dampak besar bagi dunia pendidikan, salah satunya yaitu inovasi media pembelajaran. Adanya inovasi media pembelajaran, guru bisa menambah motivasi belajar siswa yang nantinya juga akan berdampak pada hasil belajar siswa. Penelitian ini mengembangkan media pembelajaran interaktif berbasis website google sites dalam meningkatkan hasil belajar pada mata pelajara IPS di SMP Islam Ngebruk. Metode yang digunakan yaitu metode R&D. Penelitian ini menggunakan 3 kelas yaitu kelas uji coba, eksperimen, dan kelas kontrol ada 20 siswa. Hasil yang didapatkan pada kelas eksperimen melalui pre test post test yaitu nilai pretes 77,8 postes 82,7. Kelas kontrol nilai pretes 73,2 postes 80,6. Untuk penilaian validasi ahli media mendapatkan nilai 94%, ahli materi, 78%, guru IPS 78%, respon siswa 80%-100%. Bisa disimpulkan bahwa pelaksanaan media pembelajaran website google sites ini bisa meningkatkan hasil belajar pada mata pelajaran IPS di SMP Islam Ngebruk dikatakan media pengembangan ini layak dan tidak perlu revisi serta respon siswa yang merasa senang.